PENGARUH KOMPENSASI, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP MINAT PINDAH (TURN OVER INTENTION) PADA KARYAWAN DI PT WINNER GROUP BATAM - Josepin Harianja; Imelda Tamba; Framita Sitanggang (Ensiklopedia of Journal, 2023)
This study aims to determine the effect of compensation, work motivation and work environment on the intention to move employees. This research was conducted at PT Winner group Batam, with a total population of 130. In this study, researchers used a simple random sampling technique. In this technique, sample members were taken from the population at random without paying attention to the strata in the population. by drawing lots, selecting numbers from a list at random. so this research sample took a sample of 50 respondents, the researcher used the multiple linear regression analysis method with the SPSS version 22 program as a data processing tool. The results showed that compensation had a negative and significant effect on the intention to move (tcount=-2.806 < ttable 1.67866). The results showed that work motivation had a negative and significant effect on the intention to move (tcount=-2.630< ttable1.67866). The results showed that the work environment has a negative and significant effect on intention to move (tcount=-2.985<ttable 1.67866).The results showed that job satisfaction, work motivation, and work environment have an influence and significant on interest in moving (Fcount = 4.080 > Ftable 2.81)